Dynamical properties of acoustic-gravity waves in the atmosphere. (May 2019) - Roy, Animesh; Roy, Subhrajit; Misra, A.P.
Abstract: We study the dynamical behaviors of a system of five coupled nonlinear equations that describes the dynamics of acoustic-gravity waves in the atmosphere. A linear stability analysis together with the analysis of Lyapunov exponents spectra are performed to show that the system can develop from ordered structures to chaotic states. Numerical simulation of the system of equations reveals that an interplay between the order and chaos indeed exists depending on whether the control parameter s 1, associated with the density scale height of acoustic-gravity waves, is below or above its critical value.